Recent transformation of economic inequality in NUTS 3 regions in Slovenia - Lučka Lorber (Geoadria, 2011)
The restructuring of the economy and transition to a market economy have had different impacts on the economic position of regions. The level of impact that changed economic and socio-political circumstances caused in the individual regions depended on various factors: the economic structure of the regions, their ability to reroute onto foreign markets, development potentials, development strategies, and their strategic decisions. Development problems are distinctive predominantly in areas suffering from structural backwardness and economic weakness with predominantly rural orientation, areas facing demographic problems, low income per inhabitant and high unemployment rate. The peripheral nature of the underdeveloped areas caused the emptying of the countryside and concentrating of the population in urban centers. Unfavorable demographic picture, emigration of the young, poor educational structure and shortage of adequate staff, and absence of strategic decisions had led to an increasing setback of the underdeveloped regions compared to the developed ones. The results of empirical analyses of division NUTS 3 regions in Slovenia into groups, taking into account the selected development indicators, lead to the conclusion that economic development has not been conducted in the context of modern understanding of balanced regional development and in accordance with the principle of integrity of implementing regional policy in the entire state territory. The existing regional developmental differences confirm the thesis that market mechanism on its own will not reduce economic inequality and substantiate the need for efficient conduct of regional policy.